Learning Behavior of Students from Broken Homes - Venia Nesti; Rici Kardo; Yasrial Chandra (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the presence of students with low learning behavior who come from broken home families. The purpose of this research is to determine 1). The learning motivation of students from broken home families 2). The factors that influence the learning motivation of students from broken home families 3). The strategies used by students from broken home families to maintain their learning motivation. The type of this research is qualitative research. The key informants in this study are MMR and FM. Meanwhile, the additional informants are A, DS, and E. The data collection method used is interviews. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The research shows that the learning behavior of broken home students is still low in almost all aspects. They do not yet have a study routine, are less independent, often procrastinate, and are easily distracted. In terms of thinking, students tend to only memorize, forget quickly, rarely ask questions, and lack critical thinking. Learning attitudes are characterized by procrastination, excuses, and cheating, while in terms of self-control, they are not yet able to manage their emotions or study time well. Although there are differences between MMR, who are more passive, and FM, who are more active, in general, the roles of guidance counselors, parents, and schools are needed to provide intensive guidance so that students' learning behaviors can develop more effectively.